2017
DOI: 10.1016/j.biocon.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Bat use of commercial coniferous plantations at multiple spatial scales: Management and conservation implications

Abstract: Commercial plantations are primarily managed for timber production, and are frequently considered poor for biodiversity, particularly for mammalian species. Bats, which constitute one fifth of mammal species worldwide, have undergone large declines throughout Europe, most likely due to widespread habitat loss and degradation. Bat use of modified landscapes such as urban or agricultural environments has been relatively well studied, however, intensively managed plantations have received less attention, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 53 publications
5
29
0
Order By: Relevance
“…However, our sample was dominated by Nyctalus noctula (71.5%), and this differed from the other studies whereby the dominant species represented 22-56% of the recordings (Bender et al 2015;Hein et al 2009;Loeb and Waldrop 2008;Morris et al 2010;Tibbels and Kurta 2003;Vindigni et al 2009). Similar results were obtained on intensively managed Sitka spruce plantations in the UK, where nine bat species were found, although in that case activity was dominated by two species: Pipistrellus pipistrellus and P. pygmaeus (Kirkpatrick et al 2017). Although we did not find that species richness (including sonotypes) differed among stand ages, a previous study in mixed forests of Switzerland revealed that species richness was higher in gaps (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…However, our sample was dominated by Nyctalus noctula (71.5%), and this differed from the other studies whereby the dominant species represented 22-56% of the recordings (Bender et al 2015;Hein et al 2009;Loeb and Waldrop 2008;Morris et al 2010;Tibbels and Kurta 2003;Vindigni et al 2009). Similar results were obtained on intensively managed Sitka spruce plantations in the UK, where nine bat species were found, although in that case activity was dominated by two species: Pipistrellus pipistrellus and P. pygmaeus (Kirkpatrick et al 2017). Although we did not find that species richness (including sonotypes) differed among stand ages, a previous study in mixed forests of Switzerland revealed that species richness was higher in gaps (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Previously, we found evidence of P. pipistrellus and P. pygmaeus making widespread use of three large, predominantly Sitka Spruce (Picea sitchensis) plantations in Scotland and Northern England, with all other species in this geographic range also detected, albeit in low numbers (Kirkpatrick et al, 2017). There was also evidence that Pipistrellus spp.…”
mentioning
confidence: 82%
“…However, often these studies are carried out in areas of extremely low conifer cover (e.g. conifer cover of less than 3%, Davidson-Watts and Jones, 2005;Davidson-Watts et al, 2006) and there is growing evidence that certain bat species are able to make use of intensively managed non-native plantations in landscapes dominated by plantations (Charbonnier et al, 2016;Cistrone et al, 2015;Kirkpatrick et al, 2017;Mortimer, 2006;Russo et al, 2010). While the impacts of logging forests have been investigated for a number of different bat species worldwide (e.g New Zealand: Parsons, 2010a, 2010b; USA: Grindal and Brigham, 1998;Australia: Law and Law, 2011), much of the previous work has concentrated primarily on old growth or native forests (Dodd et al, 2012;Grindal and Brigham, 1998;Loeb et al, 2006;Loeb and O'Keefe, 2011;Menzel et al, 2002;Patriquin and Barclay, 2003).…”
mentioning
confidence: 99%
See 2 more Smart Citations